New records of callianassid ghost shrimp (Crustacea: Decapoda: Axiidea) from reducing environments in Kyushu, southwestern Japan - Komai, Tomoyuki; Fujiwara, Yoshihiro (Zootaxa, 2012)
This paper reports on two species of callianassid ghost shrimps collected from reducing environments in Japan. Cheramuscavifrons n. sp. is described on the basis of five specimens from an invertebrate community associated with mass sinkingof whale carcasses implanted off Cape Nomamisaki, Kagoshima Prefecture, Japan, at depths of 219–254 m. This newspecies is compared with Cheramus spinophthalmus (Sakai, 1970), Callianassa aqabaensis Dworschak, 2003 andCallianassa acutirostella Sakai, 1988. The generic assignment of the new species is provisional, reflecting the flux stateof the taxonomy of the family. Nihonotrypaea thermophila Lin, Komai & Chan, 2007, originally described fromhydrothermally influenced field off northeastern Taiwan, is first recorded from outside the type locality, based on a singlespecimen from hydrothermally influenced field in Kagoshima Bay, where the siboglinid tube worm Lamellibrachia satsuma Miura, Tsukahara and Hashimoto, 1997, is abundant.